1985
DOI: 10.1111/j.1365-2265.1985.tb00168.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Family With Dexamethasone‐suppressible Hyperaldosteronism: Aldosterone Unresponsiveness to Angiotensin Ii

Abstract: A family with nine siblings in which three siblings have been shown to have dexamethasone-suppressible hyperaldosteronism was studied. All three showed no significant changes of plasma aldosterone during angiotensin II infusion at incremental rates under baseline conditions. After dexamethasone administration (2 mg/d for 4 weeks) plasma renin activity (PRA) rose to normal-supranormal range, while plasma and urinary aldosterone were maintained at low-normal levels. No restoration of aldosterone response to angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 23 publications
0
14
1
1
Order By: Relevance
“…The B/aldosterone ratio was also not different from normal in baseline conditions (15 vs 13, expressed on an equimolar basis), but was greatly lower than normal after ACTH (30 vs 84), reflecting the hyper-responsiveness of aldosterone to ACTH stimulation typical of this disease. 8,17 Moreover, a similar marked ACTH-induced decrease of B/aldosterone ratio due to aldosterone hyperresponse also occurred in the younger sister and in the father with GRA (45 and 20 vs 84, respectively). This steroid hormone pattern is in disagreement with findings in other studies of a deficient 11b- Different phenotypes in GRAhydroxylation in GRA, 18 but is in accordance with an increased aldosterone synthase activity in this condition.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The B/aldosterone ratio was also not different from normal in baseline conditions (15 vs 13, expressed on an equimolar basis), but was greatly lower than normal after ACTH (30 vs 84), reflecting the hyper-responsiveness of aldosterone to ACTH stimulation typical of this disease. 8,17 Moreover, a similar marked ACTH-induced decrease of B/aldosterone ratio due to aldosterone hyperresponse also occurred in the younger sister and in the father with GRA (45 and 20 vs 84, respectively). This steroid hormone pattern is in disagreement with findings in other studies of a deficient 11b- Different phenotypes in GRAhydroxylation in GRA, 18 but is in accordance with an increased aldosterone synthase activity in this condition.…”
Section: Discussionmentioning
confidence: 84%
“…6,7 Scarce data are available on the intrafamily variation of phenotype in patients with genetically proved GRA. While in the family previously reported by us 8 and in that described by Rich et al, 9 the penetrance of hypertension and aldosteronism was high in all affected pedigree members, in the family of Gates et al 10 and in another one more recently reported by us, 11 the great majority of affected members had mild hypertension and normal biochemistry, including serum potassium. Here we report a new family of six members in which three subjects have been identified as possessing the same type of CYP11B1/CYP11B2 chimaeric fusion, but display diverse biochemical and clinical phenotypes.…”
Section: Introductionmentioning
confidence: 76%
“…23 With dexamethasone treatment, however, plasma aldosterone did rise as a function of plasma ANG II levels. The lack of response without dexamethasone treatment is compatible with indirect evidence that aldosterone does not rise during ambulation in subjects with dexamethasone-suppressible hyperaldosteronism 24 and is explained by down-regulation of adrenal ANG II receptor number as a consequence of suppression of renin and angiotensin due to sodium retention.…”
Section: Figure 5 Relationship Between Plasma Concentrations Of Angimentioning
confidence: 99%
“…2 Subsequently it was shown to be inherited in an autosomal dominant fashion and approximately 100 cases were reported in the world literature up to the early 1990's. [3][4][5][6][7][8][9] The most common presentation of GRA used to be the discovery of asymptomatic severe hypertension, especially in infancy or early adulthood. With the ability to identify individuals by genetic or biochemical testing, much milder or earlier clinical forms are being described.…”
mentioning
confidence: 99%
“…As a result, plasma aldosterone levels do not increase and plasma renin activity (PRA) remains suppressed in response to upright posture or to an infusion of angiotensin II. 6,8,[11][12][13][14] In establishing the differential diagnosis of primary aldosteronism, patients should have supine PRA, aldosterone and cortisol measured at 08.00 h and again erect at 12.00 h. A fall in plasma cortisol (and by inference ACTH) together with a concomitant fall in plasma aldosterone across the same period is highly suggestive of GRA. A single measurement may not be representative, and this procedure should be repeated on at least two occasions.…”
mentioning
confidence: 99%